Requirements to justify breastfeeding in public: a philosophical analysis - Fiona Woollard (BMC, 2019)
Abstract Background It may be tempting for breastfeeding advocates to respond to challenges of breastfeeding older children or breastfeeding in public, by pointing out the nutritional or developmental benefits of breastfeeding, or by noting that breastfeeding is often extremely discreet. Such responses may concede more than they should: by focusing on rebutting the empirical claim, breastfeeding supporters may end up implicitly accepting two presuppositions about breastfeeding. First, the presupposition that breastfeeding requires justification in terms of health or developmental benefits to the child, and second, the presupposition that breastfeeding in public is only acceptable if assumed standards of discretion are met. Discussion This paper aims to use the methods of analytic philosophy to: (a) show how, if left unchallenged, these implicit assumptions can become part of the pragmatic presuppositions of the conversation, so that the discussion proceeds taking their acceptance for granted, (b) argue that we can expect these presuppositions to have negative effects on all mothers, no matter how they feed their babies, and on the tenor of public discussion of infant feeding, (c) reconstruct the reasoning that might underlie these presuppositions and show that this reasoning is mistaken, and (d) show that recognising breastfeeding as a family way of life and a loving interaction between parent and child gives rise to a moral right to breastfeed in public without social sanction, whether one is able to breastfeed discreetly or not. Conclusions Mothers have an unconditional, moral right to breastfeed and to feel welcome to breastfeed in public even if they are not able to breastfeed 'discreetly'.